BASIC IDEAS FOR DETERMINING DEATH CRIMINAL THREATS IN LAW NUMBER 35 OF 2009 ON NARCOTICS - Malik, Faissal (Ganesha Law Review, 2019)
The basic idea of ​​using the threat of capital punishment against perpetrators of "producers and dealers" regulated by Law Number 35 of 2009 concerning Narcotics as a policy to combat narcotics crime is based on several reasons, including: First, narcotics crimes committed by perpetrators of "producers and distributors "Organized and systematic patterns, because they are carried out with a very sophisticated modus operandi and have networks to circulate and trade for purely economic interests, so it is not easy to uncover and prove it. Second, the circulation and abuse of illicit drug trafficking by perpetrators of "producers and distributors" is a threat that sooner or later gives a serious impact because it destroys young generation, destroys the nation and the state that is not less powerful than criminal acts of terrorism and corruption, due to the fact that arising from narcotics abuse has caused victims of HIV / AIDS and hepatitis, even death among the very young generation. So that the Government of the Republic of Indonesia is of the view that the actions of the perpetrators of "producers and distributors" in producing and distributing narcotics are crimes against humanity, because their actions can destroy humanity slowly but surely.